Influence Combination Therapy Benson Relaxation and Lemon Aromatherapy Against Change Pain Intensity in Post-Op Lower Extremity Fracture Patients - Nofadillah, Ira Saputri; Mugianti, Sri; Supono, Supono; Hamarno, Rudi (Indonesian Journal of Applied Health, 2025)
Pain in Lower Extremity Fracture postoperative patients is usually caused by the loss of anesthetic, so it must be addressed immediately because it can have an impact on the patient's healing process psychologically and physiologically. The purpose of this study was to determine the Effect of the Combination of Benson Relaxation Therapy and Lemon Aromatherapy on Changes in Pain Intensity of Post Op Patients with Lower Extremity Fractures in Yudistira Room, Jombang Hospital. This research method is a quasi experiment with a two group pre test - post test control group design. The population was post op lower extremity fracture patients in Yudistira Room, Jombang Hospital. Sampling using purposive sampling. The sample in this study amounted to 32 respondents who were divided into 2 experimental groups and a control group of 16 respondents. Analysis using the Wilcoxon Test of pain in experimental group respondents before treatment was given, namely experiencing moderate pain on a scale of 4-6 and in the control group on a scale of 5-6. The results of the pain score after treatment in the experimental group were mild pain on a scale of 1-2 and in the control group mild pain on a scale of 3 and moderate pain on a scale of 4. The test value obtained ap value of 0.000 was smaller than the significant value of 0.05. So that the combination of Benson relaxation therapy and lemon aromatherapy has more effect on reducing the respondent's pain scale. This research can be an alternative in providing nursing interventions in reducing pain in post op lower limb fracture patients .